EDUCAÇÃO E CONTROLE SOCIAL NA PRIMEIRA DÉCADA REPUBLICANA - Lacerda, Emelyn Mariana Pimenta (2012)
The present work aims to study the black rebellion in the years before slavery and its consequences, both social and educational. The fact of the Province of Sao Paulo has become a major coffee exporter made of it a strong enslaver center. No one can deny the influence of four centuries of slavery, nor its effects on the nation. Slavery was abolished on May 13, 1888, and this measure has launched in the streets a crowd of free blacks without any future prospects. They were not prepared to live in freedom, the society was not organized to receive them as free workers and pay for their work. Many people thought of them as lazy, loafer and riotous. They were never treated as equals, but as a mediocre and inferior race, whose immorality and excesses reach an irreversible point, if not controlled. Given this situation, it was necessary to draw up plans to curb excesses and the fury of the great mass of freedmen loose in the streets, it became an extreme urgency to use several means in order to maintain the social control, inculcating in the black people minds the harm caused by the riots, the duty of work, the abandonment of the vices. Therefore, intellectuals, politicians and major exporters (who represented the economic power of the time) started to use the various media for propagation of republican values, newspapers, political conferences, newsletters and, also, the educational system. Through reading books, educational magazine articles, addition of new disciplines to the school curriculum and even the action of the teacher in the classroom aimed at the docility of the people habits. The Republicans who took political power in the country were not only concerned in educating the few, who had access to schooling, but also, though example, educate and calm down the lazy and loafer blacks who could not attend school. Thence resulting in a great concern about the establishment of rules, organization, respect and punishments in the newly restructured school environment (AU)